2018
DOI: 10.12681/jhvms.15613
|View full text |Cite
|
Sign up to set email alerts
|

Canine Diabetic Ketosis-Ketoacidosis: A Retrospective Study of 23 Cases (1997-2013)

Abstract: ABSTRACT. The purpose of this retrospective study was to describe the historical and clinical findings, the clinicopathological abnormalities, the occurrence and nature of concurrent diseases, the treatment and outcome of 23 dogs with diabetic ketosisketoacidosis (DK-DKA). Inclusion criteria consisted of the presence of clinical signs suggestive of diabetes mellitus (DM) along with persistent hyperglycemia, glycosuria and ketonuria during the first 24 hours of hospitalization. In nineteen dogs (83%) DM had not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Previous studies have reported pancreatitis, urinary tract infections, and hyperadrenocorticism as the most common concurrent diseases in canine patients with DKA. [23][24][25] These comorbidities were also common in the present study. It is also notable that renal (21% [16/76]) and cardiac (30% [23/76]) disease were common in the present study's patient population, as these disease processes have many mechanisms through which they can affect sodium concentration, glucose concentration, and total body water content.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Previous studies have reported pancreatitis, urinary tract infections, and hyperadrenocorticism as the most common concurrent diseases in canine patients with DKA. [23][24][25] These comorbidities were also common in the present study. It is also notable that renal (21% [16/76]) and cardiac (30% [23/76]) disease were common in the present study's patient population, as these disease processes have many mechanisms through which they can affect sodium concentration, glucose concentration, and total body water content.…”
Section: Discussionsupporting
confidence: 56%
“…The percentage of patients with concurrent diseases (93% [71/76]) was higher than previously reported (up to 74%). 23,24 However, prior studies defined concurrent diseases as only those for which confirmatory testing had been performed, while the present study recorded all identified or clinically suspected problems regardless of confirmatory testing. 23,24 The broader definition in this study and the patient population presenting to our referral institution likely accounted for the increased percentage of concurrent diseases.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation